Structural and functional changes in the heart and clinical features of heart failure with preserved left ventricular ejection fraction in patients after myocardial infarction, comorbided with arterial hypertension - V. D. Syvolap; Ya. V. Zemlyaniy (Zaporožskij Medicinskij Žurnal)
Recently, much attention was paid to left ventricular diastolic dysfunction and its role in the occurrence of chronic heart failure. In patients after myocardial infarction, diastolic dysfunction often precedes systolic dysfunction and predicts prognosis. In patients after myocardial infarction, diastolic dysfunction is caused by a violation of early diastolic relaxation in the area of increasing stiffness. Diastolic dysfunction is formed by hypertrophy, fibrosis, myocardial ischemia and arterial hypertension. Given the important role of diastolic dysfunction in the formation of heart failure in postinfarction patients with concomitant arterial hypertension, the mechanisms of its impact on clinical features and structural-functional changes of the heart is an actual problem.